2013
DOI: 10.1016/j.jct.2012.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational study of the energetics of hydantoin and 2-thiohydantoin

Abstract: The standard (p°= 0.1 MPa) molar energies of combustion of hydantoin and 2-thiohydantoin were measured by static and rotating bomb combustion calorimetry, respectively. The standard molar enthalpies of sublimation, at T = 298.15 K, were derived from the temperature dependence of the vapour pressures of these compounds, measured by the Knudsen-effusion technique, and from high temperature Calvet microcalorimetry. The conjugation of these experimental results enables the calculation of the standard molar enthalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
9
2
Order By: Relevance
“…The two conformers resulting from protonation at the urea carbonyl, HYH , are of identical stabilities and a proton affinity value of 828 kJ/mol is calculated. The difference observed between this estimate and the previously published value of 821.7 kJ/mol (Silva et al, ) probably arise from the missing of the proton enthalpy in the PA calculation by Silva et al Protonation at the second carbonyl oxygen leads to a structure 19 kJ/mol less stable than HYH (G4MP2 result). Again, PA( HY ) may be compared to the value determined for N , N ‐dimethyl urea (903 kJ/mol, Scheme ).…”
Section: Acids and Derivativescontrasting
confidence: 74%
See 1 more Smart Citation
“…The two conformers resulting from protonation at the urea carbonyl, HYH , are of identical stabilities and a proton affinity value of 828 kJ/mol is calculated. The difference observed between this estimate and the previously published value of 821.7 kJ/mol (Silva et al, ) probably arise from the missing of the proton enthalpy in the PA calculation by Silva et al Protonation at the second carbonyl oxygen leads to a structure 19 kJ/mol less stable than HYH (G4MP2 result). Again, PA( HY ) may be compared to the value determined for N , N ‐dimethyl urea (903 kJ/mol, Scheme ).…”
Section: Acids and Derivativescontrasting
confidence: 74%
“…Recently, proton affinities for the four possible protonations sites of hydantoin HY were calculated at the G3MP2B3 level of theory (Silva et al, ) (Scheme ). The urea carbonyl is found to be the most basic site and a PA( HY ) value of 821.7 kJ/mol has been proposed.…”
Section: Acids and Derivativesmentioning
confidence: 99%
“…Despite the study made by Ribeiro da Silva et al [6][7][8] for hydantoin compounds, thermochemical data for the compounds under study in the present work were not found. Thus, the aim of this paper is to contribute to the knowledge of the thermodynamic and thermochemical properties of 5m5p and 5,5p.…”
contrasting
confidence: 73%
“…The value obtained for hydantoin was 116.1 kJ mol -1 . From this value and the reported [8] enthalpy of formation in condensed phase, which is -(448.6 ± 1.1) kJ mol -1 , the enthalpy of formation in the gas phase was obtained as -332.5 kJ mol -1 . These results agree satisfactorily with the experimental values of (116.3 ± 0.7) and -(323.3 ± 1.3) kJ mol -1 , respectively [8].…”
Section: Resultsmentioning
confidence: 90%
“…The G3 theory [28] and computationally less expensive versions of it, such as G3(MP2) [29] and G3(MP2)//B3 [30], are quantum mechanical methods that have been widely used in the study of a variety of compounds [31][32][33][34], rotational barriers [35,36], and mechanisms [37][38][39]. However, the size of molecular systems continues to be a limiting factor that prevents the more general use of Gaussian-n theories.…”
Section: Methodsmentioning
confidence: 99%